O cotidiano dos viajantes nos caminhos fluviais de Mato Grosso no século XIX - Edil Pedroso da Silva (Navigator)
The This study aims to reconstruct the daily life of the passenger and the crew of vessels that during the XIX th century travelled on the seas and rivers between Rio de Janeiro, Cuiabá, Cáceres and Corumbá, in Mato Grosso. Thorough this study, it was possible to understand and go inside those boats and from them get to know the travelers, the kind of vessels used to the trips, the passengers, the crew's lives, the picturesque scenes, the accidents, the food and welfare of these especial people, during those adventurous voyages.